Detailed investigation of two high‐speed evolved Galactic stars. Issue 3 (9th December 2021) - Matas Pinto, Aroa del Mar; Caffau, Elisabetta; François, Patrick; Spite, Monique; Bonifacio, Piercarlo; Wanajo, Shinya; Aoki, Wako; Monaco, Lorenzo; Suda, Takuma; Spite, François; Sbordone, Luca; Lombardo, Linda; et al.
Abstract: The study of metal poor stars provides clarification and knowledge about the primordial Universe. Specially, halo stars provide explanations of the nature of the first generations of stars and the nucleosynthesis in the metal‐poor regime. We present a detailed chemical analysis and determination of the kinematic and orbital properties of two stars characterized by high speed with respect to the Sun. We analyzed two high‐resolution Subaru spectra employing the MyGIsFOS code, which allows to derive the detailed chemical abundances for 28 elements (C, N, O, Na, Mg, Al, Si, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sr, Y, Zr, Ba, La, Ce, Pr, Nd, Sm, and Eu), and abundance from two ionization states in the case of four elements (Ti, Cr, Fe, and Zr). TYC 622–742–1 and TYC 1193–1918–1 are metal‐poor stars ([Fe/H] of −2.37 and −1.60), they are similar in the chemical pattern with respect to Fe, they are α enhanced and show a slight excess in Eu abundance. Both giant stars are poor in C and rich in N, as expected for evolved stars, and this fact is supported by the low 12 C / 13 C isotopic ratio in TYC 1193–1918–1. Nevertheless, the C abundance of TYC 622–742–1 is particularly low. TYC 622–742–1 and TYC 1193–1918–1 have a similar chemical composition to the other Galactic halo stars of comparable metallicity. According to their kinematics, both stars belong to the Galactic halo, but they are not a part of the Gaia‐Sausage‐Enceladus structure.